Global evidence of aerosol-induced invigoration in marine cumulus clouds - Douglas, A; L’Ecuyer, T (European Geosciences Union, 2021)
Aerosol–cloud–precipitation interactions can lead to a myriad of responses within shallow cumulus clouds, including an invigoration response, whereby aerosol loading results in a higher rain rate, more turbulence, and deepening of the cloud layer. However few global studies have found direct evidence that invigoration occurs. The few satellitebased studies that report evidence for such effects generally focus on only the deepening response. Here, we show evidence of invigoration beyond a deepening response by investigating the effects of aerosol loading on the latent heating and vertical motion profiles of warm rain. Using latent heating and vertical motion profiles derived from CloudSat radar observations, we show precipitating cumulus clouds in unstable, polluted environments exhibit a marked increase in precipitation formation rates and cloud top entrainment rates. However, invigoration is only discernible when the stability of the boundary layer is explicitly accounted for in the analysis. Without this environmental constraint, the mean polluted and pristine cloud responses are indiscernible from each other due to offsetting cloud responses in stable and unstable environments. Invigoration, or suppression depending on the environment, may induce possible feedbacks in both stable and unstable conditions that could subdue or enhance these effects, respectively. The strength of the invigoration response is found to additionally depend on cloud organization defined here by the size of the warm rain system. These results suggest that warm cloud parameterizations must account for not only the possibility of aerosol-induced cloud invigoration, but also the dependence of this invigorated state on the environment and the organization of the rain system.